Understanding Perceptions about Physically Active Lifestyles among Participants in a School-sponsored “Mothers in Movement Program” in an Inner-City Community - Álvarez Bogantes, Carlos (2021)
This study is aimed at understanding perceptions regarding how physical activity impacts women who are participating in the Mothers in Movement program an initiative sponsored by two priority schools in Heredia, Costa Rica and also examines social support received by participants and their families. The goal was to obtain input to foster interventions towards increasing physical activity among sedentary adult women and their families. This study uses a qualitative approach, obtaining data through focus groups conducted among a sample of 22 persons who are stay-at-home mothers. The study results show that, at an intrapersonal level, women feel more successful and self-sufficient when they are physically active. They are also better able to control their expectations as well as their social, persuasion and modelling abilities.  On an interpersonal level, participants turned to social, instrumental, emotional and informational support and companionship when deciding to engage in physical activity. Finally, at an organizational level, the school´s support in helping coordinate and execute this project was essential to promoting physical activity. This study highlighted the success of a socio-ecological model as a starting point to help sedentary mothers and their families lead more physically active lives.